133k views
2 votes
I asked this 3 times already and it shouldn't be hard for me but it is so please help :)

I asked this 3 times already and it shouldn't be hard for me but it is so please help-example-1
User Evilpie
by
4.8k points

2 Answers

2 votes

Answer:

34

Explanation:

| 2 - 4a | - 2(b - 7)

let a = 3, b = -5

substitute a = 3, b = -5 into the equation:

| 2 - 4a | - 2(b - 7)

= | 2 - 4(3) | - 2(-5 - 7)

= | 2 - 12 | - 2(-12)

= | -10 | + 24

= 10 + 24

= 34

User Wwward
by
4.5k points
4 votes

Answer:

  • 34

Explanation:

Given

  • a = 3, b = -5
  • | 2 - 4a | - 2(b - 7)

Solution

Substitute the values of a and b

  • | 2 - 4a | - 2(b - 7) =
  • | 2 - 4*3 | - 2(-5 - 7) =
  • | 2 - 12 | - 2(-12) =
  • | -10 | + 24 =
  • 10 + 24 =
  • 34
User Korny
by
5.4k points